Mesenchymal stromal cells for steroid-refractory biopsy-proven grade III-IV acute Graft-versus-Host Disease with predominant gastrointestinal involvement - Bukauskas, Adomas; Jucaitienė, Renata; Stoškus, Mindaugas; Valčeckienė, Vilma; Bušmaitė, Greta; Slobinas, Artūras; Davainis, Linas; Šlepikienė, Inga; Trociukas, Igoris; Pečeliūnas, Valdas; Griškevičius, Laimonas; Žučenka, Andrius (Frontiers in Immunology, 2025)
IntroductionSteroid-refractory acute Graft-versus-Host Disease (SR-aGVHD) is a potentially fatal complication occurring in approximately 60-70% of severe grade III-IV GVHD cases, with a higher incidence in patients with gastrointestinal (GI) involvement. GI aGVHD is associated with poor prognosis, with a 2-year overall survival (OS) rate of only 25% in patients with stage 3-4 GI involvement. Mesenchymal stromal cells (MSC) have emerged as a promising therapeutic option due to their favorable efficacy and safety profile. However, data on bone marrow (BM)-derived MSC use in biopsy-proven grade III-IV SR-aGVHD with GI involvement, particularly in stage 3-4 cases, remain limited.MethodsThis prospective, observational, single-arm, single-center study assessed the efficacy and safety of BM-derived MSC for treating adult patients with biopsy-proven grade III-IV SR-aGVHD with predominant GI involvement. Early (1st-2nd) passage BM-derived MSC were administered weekly at a target dose of 1x106 MSC/kg in two regimens: up to three (MSC3) and six doses (MSC6).ResultsFifty-seven adult patients with biopsy-proven III-IV grade SR-aGVHD (93% with GI involvement) received MSC treatment. The overall response rate (ORR) was 39% and 42% on Days 14 and 28, respectively, with no significant differences between the two MSC groups (Day 28 ORR 38% for MSC3 and 44% for MSC6). In patients with stage 3-4 GI involvement, the ORR was 26% and 36% at the corresponding time points with comparable efficacy between the two MSC groups (Day 28 ORR 31% for MSC3 and 38% for MSC6). Day 14 and Day 28 responders had significantly higher OS compared to non-responders (52% vs. 7%, p=0.000; 54% vs. 5%, p=0.000), with a comparable OS benefit observed in patients with stage 3-4 GI involvement (45% vs. 8%, p=0.005; 42% vs. 6%, p=0.005), respectively. MSC treatment had a favorable safety profile. The one, 5 and 10-year OS rates were 27%, 24%, and 24%, respectively.ConclusionsThe grade III-IV SR-aGVHD patients, including cases with biopsy-proven severe GI involvement, had significantly better clinical outcomes if responses to MSC treatment were observed on Days 14 and 28. Intensified MSC administration schedule has failed to improve the clinical outcomes. MSC studies focusing on aGVHD prevention and (or) first-line treatment in combination with other agents should be considered.